Torque calculation method of a permanent magnet spherical motor. - Hyung-Woo Lee
This paper presents the torque calculation method of a permanent magnet spherical motor. tho calculate using the finite element method (FEM), three-dimensional (3D) FEM must be used. However, since the method requires excessive time and memory, an easier torque calculation method is the torque profile curve. We present the approximation method of the torque profile curve and show that the torque calculation result can approximate the torque obtained by 3-D FEM.
Keywords: Permanent magnet; Numerical method; Field computation